Does the video head impulse test replace caloric testing in the assessment of patients with chronic dizziness? A systematic review and meta-analysis - Vallim,Maria Gabriela Bonilha (2021)
Abstract Introduction: Caloric testing is the most frequently used test to assess peripheral vestibular function since the beginning of the 20th century. However, the video head impulse test, vHIT, has gained prominence in the field of neurotology, as it is a faster examination, easier to perform and less uncomfortable for the patient. Objective: To compare, through systematic review and meta-analysis, the proportion of altered cases between vHIT tests and caloric testing in patients with chronic dizziness, in addition to assessing the sensitivity and specificity of vHIT, with caloric testing as the gold standard. Methods: The literature search was carried out in the PubMed, Scopus, BVS-Bireme, Web of Science, Embase, Cochrane and ProQuest indexed databases, with no restrictions regarding the publication period. All articles that contained the results of the two tests were included in the evaluation of patients with dizziness. Two researchers independently conducted data selection and extraction from the studies, strictly following the inclusion and exclusion criteria defined in the research protocol. In case of disagreement during the selection, a discussion was carried out with a third evaluator. Results: Eleven of the 1293 initial articles met the eligibility criteria and were analyzed. 2670 patients were evaluated, of which 1112 (41.6%) were males and 1558 (58.4%) females, with a mean age of 51.6 years. The proportion of altered results in the vHIT was 21% (95%CI 9% --33%), and 55% in the caloric testing (95%CI 43% --67%). Conclusion: The vHIT does not substitute for caloric testing. The tests are complementary in assessing the patient with dizziness, as they describe the tonotopy of the ampullary crest at different frequency ranges of stimulation. In chronic cases, the vHIT has a low sensitivity and high diagnostic specificity in comparison to caloric testing.